The relationship between the Big Five personality traits and earnings: Evidence from a meta analysis - Melchior Vella (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2023)
The role and importance of personality traits in determining labour market outcomes remain largely contested. This meta-analytic review addresses the question of whether the Big Five traits are related to earnings. A comprehensive literature search identified 52 studies that met the inclusion criteria (1,307 regression coefficients). The findings indicate that Openness to Experience, Conscientiousness and Extraversion are positively correlated with earnings, while Agreeableness and Neuroticism are inversely correlated with earnings. The study finds that the magnitudes of the earnings effects are modest to small, show a high degree of heterogeneity and are largely scaled down after accounting for publication bias. The main contributors to the observed heterogeneity are identified as being socioeconomic background, occupation, cognitive ability, and educational attainment. The study suggests that environmental factors play an important role in the relationship between personality traits and earnings, so omitting relevant factors from the empirical model could lead to omitted variable bias in the estimates.
Keywords: 330; Wages And Earnings; Psychology; Labour Market